Assessment of Background Exposure and Additional Exposure by Human Biomonitoring - Göen, Thomas; Neumann, Hans Günter (Springer International Publishing, 2021)
Human biomonitoring means the analytical measurement of xenobiotics, their metabolites, and their reaction products (internal exposure monitoring), but also detection of specific effects in human biological molecules and materials (effect monitoring). Its purpose is the evaluation of the exposure, but also of the health risk associated with exposure, by referring to appropriate assessment values. The weight of human biomonitoring parameters is different from case to case, and depends on the linkage of the parameter with the toxic effect, e.g., xenobiotics adducts at proteins and deoxyribonucleic acid (DNA) may be linked more strongly with the carcinogenic risk compared to urinary excreted metabolites. Human biomonitoring is also able to reveal a background exposure of individuals without any identified specific exposure, which may result from various environmental sources but in some cases also endogenously from physiological processes. Independent of the source, a quantified internal exposure needs an evaluation, preferably by referring to health-based assessmfent values. In the case of nonderivability of such values, the comparison of human biomonitoring results with so-called reference values or risk-related assessment values may serve an adequate option.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Carcinogens; Exposure assessment; Hazardous substances; Human biomonitoring; Metabolites; Risk assessment; Xenobiotics